Training on STEAM learning design through kirigami, tessellation and simple robotics - Rahmadi, Imam Fitri; Putra, Yudi Yunika; Pratama, Suprayuandi (Community Empowerment, 2025)
Pedagogical and content-related issues are the main challenges in implementing Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning. Moreover, teachers have not fully understood the concept of the STEAM approach. Therefore, it is necessary to enhance their skills in designing and implementing project-based learning, as well as ensuring that learning content is connected to real-life contexts and integrated across disciplines. This community service program aims to develop STEAM learning innovations through project-based and experiential learning models using kirigami, tessellation, and simple robotics. The method is designed based on a partnership concept, grounded in pedagogical co-designing activities, consisting of four stages: pre-activity, socialization, training, and evaluation. The results indicate an improvement in teachers’ understanding of the STEAM approach. Additionally, teachers successfully enhanced their skills in designing STEAM learning using kirigami, tessellation, and simple robotics.